A comparison between the European and the Brazilian models for management and diagnosis of river basins - Pedro Bettencourt (IWA Publishing, 2021)
Water management is assuming more and more importance as freshwater resources are becoming scarce, both in quality and in quantity, across many developed and developing countries. This trend can be attributed to population growth, industrialization, growing agricultural demand, poor water management practices and climate change. In attempting to deal with the intensification of water quality- and quantity-related problems in recent decades, many countries have revised their water resource management policies and legislation, introducing new institutional frameworks and management instruments. Considering regional geographic and cultural distinctions, the present article aims at comparing the models of water resource management in the European Union (EU) and in Brazil. Institutional and legal arrangements currently in place, water planning and management instruments currently in use, assessments of water body status and watershed diagnoses were analysed. Main strengths and weaknesses of each water management system are pointed out in the conclusion. Main challenges for the water sector, and highlights of the converging and diverging points concerning water resource management systems, in each region, are discussed. Highlights Management of tropical and temperate water resources are distinct.; Management differences are due to cultural and geographic characteristics of basins.; Drainage basins were shown to be the efficient management units in both regions.; More efficient management tools are developed with comprehensive basin monitoring.; Regardless of the region, management targets are difficult to be attained.;